Characteristic Brain Imaging Findings in a Patient with Joubert Syndrome and Segmental Glomerulosclerosis - Ahmed H. Abduljabbar, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Joubert syndrome is a rare disorder inherited as an autosomal recessive trait. It has distinctive clinical features and specific brain imaging fi ndings on magnetic resonance imaging. Patients present clinically with hyperpnea, apnea, ocular abnormalities, developmental delay and truncal ataxia. In this case report, we illustrate a patient with Joubert syndrome and chronic renal failure. Magmetic resonance imaging examination revealed the characteristic "molar tooth" appearance of the brain stem, "bat-wing" shaped 4th ventricle, cleft vermis and deep interpeduncular fossa consistent with the diagnosis.